STUDI TUTUPAN DAN KERAPATAN LAMUN DI DESA SITARDAS KECAMATAN BADIRI KABUPATEN TAPANULI TENGAH (Study of Seagrass Coverage and Density at Sitardas Village Badiri Subdistrict Tapanuli Tengah Distric) - Amos Christoper Meliala; Hasan Sitorus; Zulham Apandy Harahap (AQUACOASTMARINE, 2017)
Research was carried out at the Sitardas Village, Badiri Subdistrict, Tapanuli Tengah District on April 2016. The research aim were to know covered percentage and density of seagrass at Sitardas Village, Tapanuli Tengah District. Seagrass observations using transect quadratic method. In this research, found 4 species of seagrass consist of Enhalus acoroides, Cymodocea serrulata, Cymodocea rotundata and Halophila ovalis. Physical-chemical parameter of waters obtained temperature ranges 28-29°C, water depth ranges 50-95 cm, salinity ranges 27-29 ppt, pH ranges 7.8-8.0, speed of water flow ranges 0.10-0.70 m/s, DO ranges 5.1-6.4 mg/l and water transparency was 100%. Type of substrates obtained were loam sandy, silty loam and sandy loam. The mean seagrass covered percentage was 5.24%, Seagrass covered percentage per species obtained Enhalus acoroides was 4.99%, Cymodocea serrulata was 0.19%, Cymodocea rotundata was 0.06% and Halophila ovalis was 0%. Seagrass density of each spesies were Enhalus acoroides 26 individual/m², Cymodocea serrulata 5 individual/m², Cymodocea rotundata 3 individual/m² and Halophila ovalis 2 individual/m². Dispersial pattern seagrass Enhalus acoroides and Cymodocea serrulata was uniform while Cymodocea rotundata and Halophila ovalis was clumped.Keywords: Covered percentage, Density, Seagrass, Sitardas Village